Preventing mother to child transmission : follow up for babies and infant feeding for HIV positive mothers in Khomas region, Namibia - Friis, Fredericka Ndeshi (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.